FENOMENA INTERAKSI PEREMPUAN DI MEDIA SOSIAL DALAM PERSPEKTIF HUKUM ISLAM - Akhmad Rudi Maswanto (Program Studi Hukum Keluarga Islam, Fakultas Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
Questioning women's behavior is actually not an easy task for the author, there is a moral burden where it seems that when women are positioned as research objects, there will be a stigma that men are